2020
DOI: 10.3390/ijms21010349
|View full text |Cite
|
Sign up to set email alerts
|

Senile Osteoporosis: The Involvement of Differentiation and Senescence of Bone Marrow Stromal Cells

Abstract: Senile osteoporosis has become a worldwide bone disease with the aging of the world population. It increases the risk of bone fracture and seriously affects human health. Unlike postmenopausal osteoporosis which is linked to menopause in women, senile osteoporosis is due to aging, hence, affecting both men and women. It is commonly found in people with more than their 70s. Evidence has shown that with age increase, bone marrow stromal cells (BMSCs) differentiate into more adipocytes rather than osteoblasts and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(96 citation statements)
references
References 160 publications
(177 reference statements)
3
90
0
3
Order By: Relevance
“…An additional factor playing a role in the lower osteogenic potential of osteoporotic MSCs is that in senile osteoporosis, MSCs undergo cellular senescence resulting in a growth arrest [57].…”
Section: Mscs As a Potential Stem Cell Therapy For Bone Degenerationmentioning
confidence: 99%
“…An additional factor playing a role in the lower osteogenic potential of osteoporotic MSCs is that in senile osteoporosis, MSCs undergo cellular senescence resulting in a growth arrest [57].…”
Section: Mscs As a Potential Stem Cell Therapy For Bone Degenerationmentioning
confidence: 99%
“…Osteogenesis and cellular senescence of BMSCs play great roles in bone formation (Qadir et al, 2020). In this study, our data showed ASPH longest isoform promoting the osteogenesis while inhibiting cellular senescence, indicating it potentially results in an elevated capacity of bone formation.…”
Section: Discussionmentioning
confidence: 49%
“…Several data confirm that aging is characterized by the reduction of bone tissue which is replaced by bone marrow adipose tissue, as a consequence of decreased osteoblastogenesis and a concomitant enhanced adipogenesis from BMSCs [59] (Table 2). It has been shown that the changes in BMSC proliferation and the switch of differentiation toward the adipogenic lineage is one of the main physio-pathological mechanisms of senile osteoporosis [60,61]. BMSCs deriving from elderly subjects present a decline of osteoblastogenesis and a tendency for adipogenic differentiation [62].…”
Section: Bmscsmentioning
confidence: 99%